Effects of stocking density on growth and survival of Thai pangas (Pangasius hypophthalmus Sauvage, 1878) fry in net cages in a commercial fish farm in Noakhali, Bangladesh - Islam, Ariful; Habib, Ahasan; Hossain, Jakir Md. Hossain; Tumpa, Israt Jahan; Haque, Ahnad Tausif Ul; Hossain, Zakir (Fundamental and Applied Agriculture, 2019)
The present study was conducted to determine the growth performance of Thai pangas (Pangasius hypophthalmus) in the cage culture system (4.6 × 1.5 × 1.4 m3) of Globe Fisheries Ltd., at Subornachor under Noakhali, Bangladesh for a period of 45 days. The net cages were divided into three treatment groups at the density of 200 fishes m−3, 400 fishes m−3 and 600 fishes m−3 for treatment T1, T2 and T3, respectively. The initial weight of P. hypophthalmus fry was 0.19 ± 0.007g and stocked the fry in net cage. After acclimatization, the fry fed with formulated diet containing 28% gross protein level twice a day at the rate of 5% body weight. The diet was consisted of fishmeal, mustard oil cake, rice bran, wheat bran, vitamin and salt. The water quality parameters were recorded throughout the study period and temperature, dissolved oxygen and pH were ranged 28.3–32 ◦C, 8.0–8.5 mg L−1 and 7.4–8.3, respectively. The results showed that the growth performance of P. hypophthalmus was found higher in low stocking density after 45 days of rearing. Finally, fish attained 0.2 ± 0.007 g, 0.17 ± 0.007 g, and 0.09 ± 0.06 g in mean weight gain and 1.8 ± 0.04 cm, 1.6 ± 0.07 cm, 1.2 ± 0.14 cm in mean length gain, 0.92 ± 0.006, 0.49 ± 0.005, 0.49 ± 0.003 in specific growth rate, 1.93 ± 0.23, 2.23 ± 0.19, and 3.05 ± 0.13 in food conversion ratio and 95 ± 0.02, 85 ± 0.02, and 81 ± 0.02% in survival rate in the treatment T1, T2 and T3, respectively.